2018
DOI: 10.1136/esmoopen-2018-000335
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular screening by next generation sequencing reveals a distinctive mutational profile of KIT/PDGFRA genes and novel genomic alterations: results from a 20-year cohort of patients with GIST from north-western Greece

Abstract: IntroductionGastrointestinal stromal tumours (GIST) are mesenchymal neoplasms that usually carry an activating mutation in KIT or platelet-derived growth factor receptor alpha (PDGFRA) genes with predictive and prognostic significance. We investigated the extended mutational status of GIST in a patient population of north-western Greece in order to look at geopraphic/genotypic distinctive traits.Patient and methodsClinicopathological and molecular data of 38 patients diagnosed from 1996 to 2016 with GIST in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
2
26
0
4
Order By: Relevance
“…In line with this fact, all metastasized GIST in our study exclusively showed KIT mutations. Our analysis further revealed that the majority of KIT mutations were located in exon 11 (88%), followed by mutations in exon 9 (8%), which is in accordance with previous studies [8, 15]. Almost all of our cases showed only 1 mutation, except for 2 cases harboring concomitant KIT mutations.…”
Section: Discussionsupporting
confidence: 92%
“…In line with this fact, all metastasized GIST in our study exclusively showed KIT mutations. Our analysis further revealed that the majority of KIT mutations were located in exon 11 (88%), followed by mutations in exon 9 (8%), which is in accordance with previous studies [8, 15]. Almost all of our cases showed only 1 mutation, except for 2 cases harboring concomitant KIT mutations.…”
Section: Discussionsupporting
confidence: 92%
“…As a matter of fact, large deletions involving exon-flanking regions can be missed through allelic dropout while low-allelefraction mutations are routinely overlooked by conventional Sanger sequencing due to the inherent detection limit of the approach. Indeed, a low frequency KIT mutation was already reported in a previous study made with an amplicon sequencing approach, where an exon 11 V561D was described at 9% allele frequency in a GIST specimen (22). More importantly, a recent FIGURE 3 | Analysis of KIT-specific gene expression in GIST_260.…”
Section: Discussionmentioning
confidence: 79%
“…According to previous literature BRAF mutations generally do not occur with KIT or PDGFRA mutations (Rossi et al, 2016) but in our group one patient had a BRAF mutation along with a KIT mutation and another patient harboured a BRAF mutation along with a PDGFRA mutation. A previous study by Mavroeidis et al, (2018) has also documented the occurrence of such concomitant mutations. Besides the dissimilarities discussed above we also observed the following similarities between the results of our study and the results published previously.…”
Section: Discussionmentioning
confidence: 92%